Fasciola hepatica phenotypic characterization in Andean human endemic areas: Valley versus altiplanic patterns analysed in liver flukes from sheep from Cajamarca and Mantaro, Peru. - Valero, M.A. (2012)
Fascioliasis is a zoonotic parasitic disease caused by Fasciola hepatica and Fasciola gigantica. Of both species, F. hepatica is the only one described in the Americas, mainly transmitted by lymnaeid snail vectors of the Galba/Fossaria group. Human fascioliasis endemic areas are mainly located in high altitude areas of Andean countries. Given the necessity to characterize F. hepatica populations involved, the phenotypic features of fasciolid adults infecting sheep present in human fascioliasis endemic areas were analysed in the Cajamarca Valley and Mantaro Valley (valley transmission patterns) and the northern Bolivian Altiplano (altiplanic transmission pattern). A computer image analysis system (CIAS) was applied on the basis of standardized measurements. The aforementioned highland populations were compared to standard lowland natural and experimental populations of European origin. Liver fluke size was studied by multivariate analyses. Two phenotypic patterns could be distinguished in F. hepatica adult size: the valley pattern (Cajamarca and Mantaro, Peru) and the altiplanic pattern (northern Altiplano, Bolivia). Results showed that the Andean valley population and European standard populations presented a phenotypic homogeneity. The Altiplano population showed a large size range with a pronouncedly lower minimum size indicating that uterus gravidity is reached at a smaller size than in valley populations. The results of this study demonstrate that there is no apparent relationship between the shape of fasciolid adults with regard to altitudinal difference or geographical origin and that allometry-free shape appears as a more stable trait than size in fasciolid species. Results are analysed in terms of intensity/crowding effect aspects and permanent/seasonal transmission characteristics.